Design and synthesis of beta-peptides as antimicrobial agents or adjuvants - Si, Zhangyong (Nanyang Technological University, 2019)
Most antibiotics were discovered five to seven decades ago, and they underpin many modern medical interventions such as surgery, cancer therapy, etc. However, no new class of antibiotics against Gram-negative bacteria has been discovered over the last 50 years. Meanwhile, bacteria mutate and develop resistance towards all known classes of antibiotics quickly, usually in about a year from their initial hospital use. Now, carbapenem-resistant Gram-negative bacteria head the World Health Organization (WHO) list of pathogens for which new antibiotics are critically needed. Moreover, dissemination of mcr-1 gene leading to plasmid-mediated colistin resistance has magnified the threat of carbapenem-resistant Gram-negative bacterial infection. Antimicrobial resistance in Gram-negative bacteria is now a global healthcare crisis. Antimicrobial peptides (AMPs) targeting the bacterial membrane are thought to be the last frontier in antibacterial development. Despite the initial excitement, the translation of AMPs from bench to bedside has shown limited success. Amongst various reasons, the primary challenges lie in the potential toxicity, peptide stability, and high production cost. Synthetic peptidomimetics that avoid the shortcomings of AMPs have been extensively explored. Amongst them, Beta(β)-peptides are the most promising alternatives because of their structural advantages. In this project, a series of β-peptides have been prepared as promising antimicrobial agents or adjuvants to potentiate other conventional antibiotics against multiple Gram-negative bacteria, including the carbapenem- and colistin-resistant Gram-negative clinical isolates. First, we developed a novel strategy to synthesize a glycosylated cationic block β-peptide via the one-pot one-shot anionic ring-opening block copolymerization and one-pot globally deprotection strategy and applied them as potential antimicrobial agents. The glycosylation block contributes towards improving the in vitro toxicity and in vivo pharmacokinetic profile and biodistribution, leading to a compound that is absent of acute toxicity at the tested concentration, intrinsically resistant to proteolysis and easy to manufacture, all of which overcome the primary limitation of natural AMPs for translation. In the following work, we found that the optimized glycosylated cationic block β-peptide PAS8-b-PDM12 sensitized all the Gram-negative bacteria in the highest priority list of ESKAPE† to numerous antibiotics by reversing two intrinsically resistant mechanisms. The synergistic combination activity was also validated by various clinically relevant infection models in mice, including wound infections, neutropenic lung infections and bacteremia infections. In the last part, we presented an N-terminal amination of β-peptide with high direct bactericidal potency against all resistant sub-populations of Gram-negative superbugs, including genetically multi-drug resistance, biofilm and persisters, without resistance and toxicity at the tested concentration. Both the biocompatibility and antimicrobial potency of N-terminal amination of β-peptide (named NH2(N)-P) were validated in the in vivo mouse study. In summary, we showed that well-designed β-peptides could be tuned to achieve low toxicity, high antimicrobial potency, and the ability to synergize classical antibiotics in in vivo studies. β-peptides with their low toxicity, high proteolysis resistance and our newly developed synthetic strategies may offer solutions to overcome the antibiotic resistance of Gram-negative bacteria for which new classes of antibiotics are in urgent demand.